The effect of post-exercise oral glutamine supplementation on a subsequent cycling time to exhaustion test: A randomized double blind placebo-controlled crossover trial - Clayton, Z. S.; Braden, B.; Kern, M. (International Journal of Applied Exercise Physiology, 2020)
Prolonged exercise decreases plasma concentrations of glutamine, which may be linked to performance decrements. Thus, we tested the hypothesis that the addition of L-glutamine (0.3g/kg bodyweight) to post-exercise carbohydrate supplementation would preserve plasma L-glutamine throughout exercise and improve performance on a subsequent cycling time to exhaustion (TTE) test in male and female experienced cyclists, relative to carbohydrate (61g glucose polymer) alone. Using a randomized, double-blinded, cross-over design, participants completed: Visit 1, an initial VO2 max test (to determine exercise intensity); Visit 2-3, followed bya high-intensity cycling bout (30 min at 70% VO2max, 6 x 1 minute sprints at 140% VO2 max, 45 min at 70% VO2max)consumed GLN or PLC, rested for 2h, then completed a TTE test (cycle at 80% VO2max until no longer maintaining 100 RPM). Blood was sampled at baseline, following 2h of recovery and following the TTE test. Despite differences (P < 0.05) in plasma glutamine concentrations between groups following the 2h recovery, no difference in TTE was detected.